Relacje rynkowe jako element strategicznych zasobów przedsiębiorstwa - Sudolska, Agata (Market Realtionships as the Part of Strategic Resources of a Firm, 2008)
"On the contemporary market, one can observe that the firm’s success is strongly related to the ability of quick reaction to the changes appearing in the environment. This ability results from having a wide net of different relationships with other market actors, such as suppliers, buyers, R+D institutions, etc. Such relationships are important elements of strategic resources of a firm. The paper is an attempt to show the idea and importance of relationships as strategic resources ofan enterprise."
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 357-364